PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Rekha Wahyusyah; Ristanti Akseptori; Arfiana Dewi (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
The purpose of this study was to analyze the effect of work environment on employee performance through job satisfaction. The research used a saturated sample. The samples amounted to fifty-one permanent employees. The type of research used explanatory research is quantitative. The data was collected using a questionnaire. The data analysis techniques used are validity test, reliability test, classical assumption test, simple linear analysis test, path analysis, and sobel test. The results of this study showed that there is a positive influence between the work environment on employee performance. There was a positive influence between the work environment on job satisfaction. Job satisfaction has a positive effect on employee performance. The results of testing with job satisfaction as an intervening variable between the work environment and employee performance proved to have no effect. The implications of this research are important for companies to pay attention to work environment conditions and increase job satisfaction so as to improve employee performance.